Aesthetic Appreciation, Library Patronage, and Academic Progression in Southwest - Bakrin, Sirajudeen Femi; Bakare-Fatungase , Oluwabunmi Dorcas (Communicate: Journal of Library and Information Science, 2024)
This study examines the perception of users on the impact of aesthetic appreciation and human environment on library patronage cum academic performance in Southwest Nigerian university libraries. The survey method was used to collect data from respondents. Eighteen universities were purposely selected to represent federal, state, and private ownership in the six states. Random sampling was further used to select two thousand six hundred (2600) respondents distributed at 40%, 40%, and 20% among the three categories of universities. A structured questionnaire was administered to the respondents via the university libraries. One thousand three and thirty-seven (1337) copies were returned and found eligible for analysis. Findings show that the architectural designs of the libraries measure up to the expectations of the users despite some deficiencies in interior decoration, lighting, and landscaping of the outer environment. Also, there is a formidable impact of library aesthetics on library patronage cum academic performance (increased visitations, improved proficiency in courses, acquisition of additional skills and success in class tests). The library should therefore collaborate with other stakeholders to make provisions for the observed shortcomings.